Revision of the endemic South African genus Moegistorhynchus Macquart (Diptera: Nemestrinidae), with a species key, description of three new species and comments on pollination biology and biogeography - Barraclough, David A.; Colville, Jonathan F. (Zootaxa, 2024)
The genus Moegistorhynchus Macquart is revised and its relationships are discussed. The genus is distributed across lowland and montane areas of the Western and Northern Cape provinces, extending from Cape Town (Western Cape province) in the south to Port Nolloth (Northern Cape province) in the north. Three new species are described from Western Cape specimens: Moegistorhynchus manningi sp. nov. (Stettynsberg and Hottentots Holland mountains); M. strillii sp. nov. (Groot Winterhoek mountains); and M. turneri sp. nov. (Groot Winterhoek mountains and Waboomsberg). The four known species of the genus are redescribed: M. braunsi Bequaert, 1935; M. brevirostris (Wiedemann, 1821); M. longirostris (Wiedemann, 1819); and M. perplexus Bequaert, 1935. Moegistorhynchus longirostris and M. brevirostris are the only two species which extend their distribution northwards into the Northern Cape. There is marked intraspecific variation in M. perplexus and it may represent a species complex. Moegistorhynchus braunsi and M. strillii sp. nov. are possibly extinct. All species are fully illustrated, inclusive of the male postabdomen, where possible. A comprehensive identification key to the species is presented as is a distribution map, with some commentary on pollination biology and biogeography.